Consciousness about Informed Consent amongst the Researcher in a Postgraduate Institute of Bangladesh (Journal of Medicine, 2008)
To assess the consciousness about informed consent (IC) of the researchers, a study was conducted in a postgraduate institute in Dhaka, Bangladesh from Dec' 2003 to Jan' 2004. A total of 39 researchers responded properly. All subjects were doctors who have completed a research work previously. A written questionnaire was given to the respondents to answer the questions about IC and then it was collected properly with the answer of the participants. The data was analyzed statistically. Most of the respondents 84.60% agreed that IC is a written consent and 94.90% respondents agreed that it includes risk and benefit. Maximum participants (97.40%) agreed that child's consent is not valid for a study, 89.70 % researchers agreed that confidentiality should be included in IC and 76.90% agreed that IC should include the duration of the study. 71.60% respondents agreed to give autonomy to the subject, 48.70% disagreed that the witness is necessary during taking IC, 66.70% respondents took IC from the study subjects during their study & 33.30 % had not taken any consent. From the present study, it can be concluded that most of the researchers of the concerned institute are knowledgeable about IC but many of them has no attitude to apply it in practice. As there is evidence of negligence to practice on IC during conducting research, awareness should be grown up amongst the researchers by conducting seminar, symposium and workshop to protect human rights during clinical trial. Â  DOI = 10.3329/jom.v7i2.1363 J MEDICINE 2006; 7 : 46-50 Â